Variação na regência de complementos locativos de verbos de movimento na fala de universitários da UFS - Rodrigues, Fernanda Gabrielle Costa (2021)
Since Latin, the prepositions a, for and in vary in the introduction of locative complements of movement verbs of the type of going, coming, arriving and taking, as in “I returned to / at / to the university”. In Brazilian Portuguese, this phenomenon is associated with the speaker's schooling, the preposition for is the most productive, varying with em, and is in the process of being disused, but this process is slower in highly schooled contexts (MOLLICA, 1996; RIBEIRO, 1996; VALLO, 2003; WIEDEMER, 2008). The expansion of access to higher education in Brazil allowed contacts between students from different regions, which reverberated in the language. At the Federal University of Sergipe, as well as at other brazilian universities, students come from different regions of the state and the surrounding area, and this diversity is configured as a dialectal factor that can interfere in the variation of the locative complement of movement verbs.We assume the perspective of the Theory of Variation and Linguistic Change (WEIREINCH; LABOV; HERZOG, 2006 [1968]; LABOV, 2008 [1972], 1978, 1994) with the objective of investigating how the cultured norm of the 21st century is configured in what it says respect to the conducting of locative complements of movement verbs to answer the following question: Is there a dialectal interference in the speech of university students at UFS regarding the conducting of movement verbs? The corpus we analyzed constitutes the sample Displacements (2019/2020), composed of speeches collected from students at the Federal University of Sergipe that compose the Falares Sergipanos database (FREITAG, 2013). We control the effects of displacement, time in the course and sex (social variables) and space configuration, definitude, determination, permanence trait, narrative of speech, verb and intervening material (linguistic variables), through association tests and analysis of conditional inferences tree, applied technique to identify similar patterns of linguistic behavior (FREITAG, PINHEIRO, 2020; FREITAG, et al. 2021). 1041 contexts of locative complement of movement verbs were identified, of which 71% are governed by the preposition for, 24% by the preposition in and 5% by the preposition a. The effects of linguistic variables follow the patterns identified in previous studies (MOLLICA, 1996; RIBEIRO, 1996; VALLO (2003); WIEDEMER (2008); VIEIRA (2009); ASSIS (2011) reinforcing the ongoing change character of the phenomenon. The analysis of the conditional tree shows evidence of the categorization of prepositions for and in different functional domains, constituting itself as a disambiguation strategy to indicate the greater or lesser permanence in locatives in which it is not possible to infer, pragmatically, the delay time. As for the dialectal effects, controlled by the displacement of the speakers, students from the interior, who come to the university and return to their homes daily, make greater use of the preposition in, with 26%. Sergipe capital to study have 22% of this use; students from the capital sergipana have 20% of the preposition in. From the external community to Sergipe, students from Alagoas they show linguistic behavior similar to the pattern of the capital of Sergipe, 19% use of in, while Bahian students show divergent behavior, 35% use of in, suggesting an effect of dialectal areas for dynamizing change.